2006
DOI: 10.1055/s-2006-924738
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages and Disadvantages of Nerve Monitoring During Thyroid Surgery in Childhood

Abstract: The IONM of both RLN and EBSLN in adult surgery could be used successfully in paediatric surgery. In this study a clear and positive identification of both nerves was possible in all patients. Therefore the IONM of the RLN and EBSLN could develop into a successful and easy method for the prevention of intraoperative nerve damage during thyroid surgery in childhood and young adolescence. Assuming that a constant IONM signal represents a normal vocal cord, our evaluation showed that there is a small percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…An additional study of 11 patients undergoing surgical excision of benign or malignant thyroid disease incorporating needle electrode monitoring of both the RLN and the external branch of the superior laryngeal nerve reported transient paresis of only 1 RLN. 23 The authors of both these studies conclude that neural monitoring of the RLN was both helpful and predictive of postoperative vocal fold function.…”
Section: Commentmentioning
confidence: 99%
“…An additional study of 11 patients undergoing surgical excision of benign or malignant thyroid disease incorporating needle electrode monitoring of both the RLN and the external branch of the superior laryngeal nerve reported transient paresis of only 1 RLN. 23 The authors of both these studies conclude that neural monitoring of the RLN was both helpful and predictive of postoperative vocal fold function.…”
Section: Commentmentioning
confidence: 99%
“…Use of a nerve stimulator during superior pole dissection to identify and avoid sectioning the EBSLN has recently been described. [7][8][9][10][11][12][13] Several workers recently have found that EMG data obtained by EBSLN stimulation with standard monitoring tubes using IONM could be quantified in 70% to 80% of cases. 14,15 Motor connections between the EBSLN and the RLN allow for EMG activity to be detected by monitoring action potentials of the thyroarytenoid muscle, especially in the anterior third of the vocal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a nerve stimulator during superior pole dissection to identify and avoid sectioning the EBSLN has recently been described . Several workers recently have found that EMG data obtained by EBSLN stimulation with standard monitoring tubes using IONM could be quantified in 70% to 80% of cases …”
Section: Introductionmentioning
confidence: 99%
“…Braukhoff et al first described IONM in 53 children aged 3 to 16 years (91 nerves at risk) by placing a bipolar electrode through the cricothyroid ligament into the intralaryngeal musculature and incurred one temporary nerve palsy (1.1%) . Meyer et al used a similar technique with bipolar needles inserted into the vocalis muscle using the Neurosign 100 (Inomed GmbH, Teningen, Germany) in 11 children aged 11 to 16 years (18 nerves at risk) and had one temporary nerve palsy (5.6%) with no other complications . White et al reported experience with the Xomed NIM monitoring endotracheal tube (Medtronic, Jacksonville FL), with integrated surface electrodes resting on the true vocal cords, to perform thyroid related surgery in five adolescents aged 11 to 17 years .…”
Section: Introductionmentioning
confidence: 99%